The processing of morphology in children with and without reading disabilities - Lázaro, Miguel; Schreuder, Robert; Aceituno, Virginia (Revista de Investigación en Logopedia, 2011)
This paper presents the results of an experiment carried out to study the morphological processing of children with, and without, reading disorders. Is it the case that children use the morphological constituents of a word to understand it, and how is this usage influenced by reading ability? We have studied this issue by presenting novel complex words in a semantic definition task with eight years old children. Our results show that, even in a no time pressure task, proficient readers were better at constructing the meaning of novel complex words than children with a reading impairment. These results suggest that differences between proficient and reading disabled children coul be not only related to the lexical access, but also to the lexical and semantic processing.